Patient safety culture in surgical departments versus other departments in county hospitals of Hubei province, China: a cross-sectional survey. (October 2016) - Wang, Manli; Tao, Hongbing; Fang, Haiqing; Cheng, Zhaohui; Cai, Miao; Lin, Xiaojun; Xu, Chang
Abstract: Background: Patient safety culture affects hospital safety and performance. The Hospital Survey on Patient Safety Culture (HSOPSC) is widely used to assess the safety culture in hospital and unit level. We aimed to assess strengths and weaknesses of surgical departments compared with others in county hospitals of China with HSOPSC. Methods: A cross-sectional study was conducted in 2015 with a Chinese translation of HSOPSC being administered to 1500 staff from 19 county hospitals in Xiaogan city of Hubei province China. We compared the percentage of positive ratings and outcome dimensions (patient safety grade and number of events) between surgical departments and other departments with t tests and χ 2 tests. We explored factors affecting overall perceptions of safety, frequency of events reported, and outcome variables with multiple linear regression, two-level multiple regression, or two-level ordered logistic regression analyses. Findings: 1379 (92%) of participants completed the HSOPSC. 779 (56%) of respondents were from surgical departments. "Teamwork within units" and "organizational learning and continuous improvement" were strengths, and "staffing" and "non-punitive response to errors" were weaknesses in the surgical departments. The dimensions "non-punitive response to errors" (38·68% vs 40·61%, p=0·001), "supervisor/manager expectations and actions promoting patient safety" (69·42% vs 71·63%, p=0·013), and "hospital management support for patient safety" (61·83% vs 65·28%, p=0·027) in surgical units were lower than those in other units. Staff in surgical units reported more events than other units (mean 2·84 [SD 0·93] vs 1·72 [0·88], p=0·015); ratios of reported patient safety grades differed between surgical settings and others (p=0·010), with fewer respondents reporting patient safety grades as good or excellent in surgical units than in other departments. A clustering effect of hospital staff within hospitals existed for overall perceptions of safety, patient safety grade, and number of events reported. Four dimensions ("organizational learning and continuous improvement", "supervisor/manager expectations and actions promoting patient safety", "feedback and communication about errors", and "hospital handoffs and transitions") influenced patient safety grade and just "hospital handoff and transition" influenced events reporting in surgical units. Interpretation: Strategies that include recruitment of more staff, improve use of reporting systems of adverse events, and build a non-punitive culture should be adopted in surgical units of county hospitals in China to improve the safety culture. Gaps remain in patient safety that need to be addressed. Funding: Chinese National Health and Family Planning Commission (grant 20131577 ).